Dampak Media Sosial Tiktok terhadap Karakter Sopan Santun Siswa Kelas V di SD Negeri 3 Pahandut - Herlia Erawati; Joni Bungai; Melinda Prawati (PGSD FKIP UPR, 2025)
This study aims to determine the impact of using TikTok social media on the politeness character of fifth-grade students at SD Negeri 3 Pahandut. The background of this research is the widespread use of TikTok among elementary school students, which is feared to influence their attitudes and behaviors in daily life, especially in terms of politeness. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation involving students, teachers, and parents as informants. The results of the study indicate that TikTok usage has a positive impact in increasing students’ creativity and self-expression. However, negative impacts are more dominant, such as the use of harsh language, lack of motivation to study and complete school tasks, disrespectful behavior toward teachers or parents, and a tendency to become addicted to gadgets. Therefore, supervision from parents and teachers is essential to reinforce the values of politeness so that students can use social media wisely.